2022
DOI: 10.3233/wor-210678
|View full text |Cite
|
Sign up to set email alerts
|

The role of work stress, organizational climate, and improving employee performance in the implementation of work from home

Abstract: BACKGROUND: The spread of COVID-19 around the world has caused many undesirable effects on human health. The pandemic forced the employees to resort to Remote Work (RW)/Work from Home (WFH) according to the nature of the jobs. Consequently, organizations, business process and results are affected and organizational and commercial activities are significantly reduced. OBJECTIVE: This study investigates the impact of work stress and organizational climate on employee performance in the context of WFH in the era … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 45 publications
3
28
0
5
Order By: Relevance
“…The association between WFH and higher work output levels has been meta-analytically demonstrated (Gajendran and Harrison, 2007), although the problem of causal orientation is far from resolved. Working at home will create a more relaxed working atmosphere, as workers are free to arrange their job schedule and work environment (Pradoto et al, 2022). A person can meet his personal needs and preferences by customizing his area of work according to his personality (Razif et al, 2020).…”
Section: Work From Home and Job Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The association between WFH and higher work output levels has been meta-analytically demonstrated (Gajendran and Harrison, 2007), although the problem of causal orientation is far from resolved. Working at home will create a more relaxed working atmosphere, as workers are free to arrange their job schedule and work environment (Pradoto et al, 2022). A person can meet his personal needs and preferences by customizing his area of work according to his personality (Razif et al, 2020).…”
Section: Work From Home and Job Performancementioning
confidence: 99%
“…In Pakistan, a new survey by the Pakistan Telecommunication Authority (PTA) found that just 36.86% of the population had access to broadband Internet in 2019 (PTA, 2019;Mumtaz et al, 2021). In another study, Pradoto et al (2022) determined that, much like traditional learning, there is a satisfactory relationship between instructors and learners in distance learning, curriculum is well-designed and up-to-date, instructors are engaged and qualified with the skills and expertise required. However, the current situation varies totally from usual distance learning programs, in which all higher education institutions throughout Pakistan are required to adopt methodologies of distance learning regardless of resources (Adnan and Anwar, 2020).…”
Section: Work From Home and Job Performancementioning
confidence: 99%
See 1 more Smart Citation
“…No obstante, frente a situaciones cambiantes se pueden generar diversas reacciones poco favorables que atenten contra el ambiente laboral, estos desafíos se observan, cuando los colaboradores no saben cómo manejar estos cambios, ausencia de habilidades emocionales y sociales, como señalan Pradoto , Haryono y Wahyuningsih [12] en su investigación, donde revelaron que el entorno organizacional puede tener un efecto negativo sobre el estrés laboral (generado por las tareas y funciones propias del puesto). Según este estudio, un clima laboral desfavorable tiene un impacto negativo sobre el rendimiento del colaborador, en cambio, un clima laboral favorable promueve el mejor rendimiento de los colaboradores.…”
Section: Ahabilidades Socialesunclassified
“…Job performance could measure the achievement of employee goals and is a key element in measuring employee behavior and attitudes at work [12] . Existing studies have pointed out that employees' job performance is affected by a variety of factors, such as organizational culture [13] , organizational climate [14] , leadership style [15] , and individual motivation [16] . However, previous researches on this issue have focused on the entire employee population, while some researchers have explored the factors influencing the performance of knowledge employees, who are relatively unique in terms of their characteristics.…”
Section: Introductionmentioning
confidence: 99%